Effectiveness of Web-Based Self-Disclosure Peer-to-Peer Support for Weight Loss: Randomized Controlled Trial - Imanaka, Mie; Ando, Masahiko; Kitamura, Tetsuhisa; Kawamura, Takashi (JMIR Publications, 2013)
BackgroundObesity is one of the most common public health problems in the industrialized world as a cause of noncommunicable diseases. Although primarily used for one-on-one communication, email is available for uninterrupted support for weight loss, but little is known about the effects of dietitian group counseling for weight control via the Internet. ObjectiveWe developed a Web-based self-disclosure health support (WSHS) system for weight loss. This study aims to compare the effect of weight change between those using the WSHS and those using the email health support (EHS). MethodsThis study was designed as an open prospective individual randomized controlled trial. Eligible participants were aged 35 to 65 years with a body mass index (BMI) of ≥25.0 in their latest health examination. Participants were randomly assigned to either the WSHS group or the EHS group. Thirteen registered dietitians under the direction of a principal dietitian each instructed 6 to 8 participants from the respective groups. All participants in the WSHS group could receive nutritional advice and calculate their nutritive intake from a photograph of a meal on their computer screen from the Internet sent to them by their dietitian, receive supervision from the registered dietitian, and view fellow participants' weight changes and lifestyle modifications. In the EHS group, a participant could receive one-on-one nutritional advice and calculate his/her nutritive intake from the photograph of a meal on computer screen sent by email from his/her dietitian, without being able to view fellow participants' status. The follow-up period was 12 weeks for both groups. The primary outcome measure was change in body weight. The secondary outcome measure included changes in BMI and waist circumference. The intergroup comparison of the changes before and after intervention was evaluated using analysis of covariance. ResultsA total of 193 participants were randomly assigned to either the WSHS group (n=97) or the EHS group (n=96). Ten from the WSHS group and 8 from the EHS group dropped out during the study period, and the remaining 87 in the WSHS group and 88 in the EHS group were followed up completely. Weight loss was significantly greater in the WSHS group than in the EHS group (-1.6 kg vs -0.7 kg; adjusted P=.04). However, there were few differences in waist circumference between the 2 groups. (-3.3 cm vs -3.0 cm; adjusted P=.71). ConclusionsOur newly developed WSHS system using forced self-disclosure had better short-term weight loss results. Further study in a longer-term trial is necessary to determine what effects this type of intervention might have on long-term cardiovascular disease. Trial RegistrationUniversity Hospital Medical Information Network Clinical Trial Registration (UMIN-CTR): UMIN000009147; https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=brows&action=brows&type=summary&recptno=R000010719&language=E (Archived by WebCite at http://www.webcitation.org/6HTCkhb1p).